Yoga Mental Resilience Model based Tri Hita Karana for Enhancing Adolescent Mental Health - I Wayan Muliarta; Luh Putu Tuti Ariani; Ketut Chandra Adinata Kusuma; I Kadek Artawan (GLOBAL HEALTH SCIENCE GROUP, 2025)
The increasing prevalence of academic anxiety and mild to moderate depressive symptoms among senior high school students has become a growing mental health concern. Limited access to formal counseling services, psychological stigma, and the need for culturally contextualized non-clinical interventions highlight the urgency of developing alternative approaches grounded in local wisdom. This study aimed to design and evaluate a Tri Hita Karana-based Yoga Mental Resiliensi (YMR) model as a promotive–preventive intervention to reduce anxiety and depression among high school students. The study employed a research and development (R&D) approach, encompassing needs analysis, model design, expert validation, and limited implementation testing. Data were collected through field observations, standardized anxiety and depression questionnaires psychological assessment using a standardized and validated instrument, namely the Depression Anxiety Stress Scales–21 (DASS-21), in-depth interviews, and focus group discussions (FGDs) involving students, teachers, and relevant school stakeholders. The YMR model integrates three core components: physical postures (light-to-moderate asana), breathing techniques and mindfulness practices (pranayama and brief meditation), and positive affirmations combined with group discussions. The findings indicate that the YMR model demonstrates strong content validity, construct validity, and practical feasibility, and contributes significantly to improved emotional regulation, enhanced mental resilience, and reduced levels of anxiety and depression among students. In conclusion, Tri Hita Karana-based yoga through the YMR model represents an innovative, adaptive, and culturally relevant intervention to support adolescent psychosocial well-being in school settings.